Comparison of EI-GC-MS/MS, APCI-LC-MS/MS, and ESI-LC-MS/MS for the Simultaneous Analysis of Nine Nitrosamines Eluted from Synthetic Resins into Artificial Saliva and Health Risk Assessment - Hyungsoo Kim; Daekwan Sung; Honghyeon Yu; Daeyong Jang; Yeji Koo; Seungha Lee; Kyungmin Lim; Dalwoong Choi (Toxics, 2021)
Nitrosamines can be produced during the manufacture of rubber-type products such as pacifiers or the nipples of baby bottles. Humans can be exposed to the nitrosamines in these products when they are eluted into saliva. In this study, we compared the efficiency of electron impact ionization (EI), atmospheric pressure chemical ionization (APCI), and electrospray ionization (ESI) methods for the analysis of nine nitrosamines eluted into artificial saliva. In addition, nine nitrosamines eluted from 54 rubber-type products (rubber, thermoplastic elastomer, thermoplastic polyurethane, and polyurethane) marketed in Korea were monitored. Finally, non-carcinogenic and carcinogenic risk assessments of oral exposure to nine nitrosamines were performed based on the monitoring results. EI-GC-MS/MS performed the best for the simultaneous analysis of these nine nitrosamines with respect to overall linearity, trace analysis limit of detection (less than 1 μg), recovery (average 108.66 ± 9.32%), and precision (less than 6%), compared with liquid chromatography-tandem mass spectrometry (LC-MS/MS) (APCI and ESI) methods. Using the EI-GC-MS/MS method, these nine nitrosamines eluted into artificial saliva from 54 rubber-type products were monitored. Based on the monitoring data, risk assessment was performed by calculating the margin of exposure (MOE) for the respective nitrosamines detected. As a result, these nitrosamines were confirmed to be safe with regard to both non-carcinogenic and carcinogenic risks.